Conceptual Content Analysis: Policy Documentation for the Quality of Higher Education in Pakistan - Amna Ramzan, Ayaz Muhammad Khan, (PJE, 2023)
We are living in the age of quality competition, in marketing term, everything in the time is only alive until it sustains its quality. If something is elapsing its quality is it means that is endingits existence from the world gradually. The leading aim of the existing paper was to analyse the content related to quality and quality assurance process of higher education in Pakistan.